2007
DOI: 10.2135/cropsci2006.06.0410
|View full text |Cite
|
Sign up to set email alerts
|

QTL Analysis of ICA Bunsi‐Derived Resistance to White Mold in a Pinto × Navy Bean Cross

Abstract: Breeding for genetic resistance to white mold [Sclerotinia sclerotiorum (Lib.) de Bary] in dry bean (Phaseolus vulgaris L.) is difficult because of low heritability. To facilitate breeding, researchers have sought to identify QTL underpinning genetic resistance to white mold. We identified two QTL conditioning ICA Bunsi‐derived resistance to white mold in a pinto × navy bean (Aztec/ND88–106–04) recombinant inbred line (85 RILs) population. ND88–106–04 is a navy breeding line with resistance to white mold deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 36 publications
2
37
0
1
Order By: Relevance
“…This selection method is also well suited for marker-assisted selection (Miklas 2007;Miklas et al 2003). This breeding method is not useful, however, for the improvement of quantitatively inherited traits such as seed yield or tolerance to abiotic stress.…”
Section: Backcrossmentioning
confidence: 99%
“…This selection method is also well suited for marker-assisted selection (Miklas 2007;Miklas et al 2003). This breeding method is not useful, however, for the improvement of quantitatively inherited traits such as seed yield or tolerance to abiotic stress.…”
Section: Backcrossmentioning
confidence: 99%
“…Also, Singh et al (2007) developed A 195 using combined pedigree and bulk breeding methods. Miklas (2007) used molecular-marker-assisted selection to introgress WM-resistant QTL located on chromosome 7 in G 122 and 8 in NY6020-4. Similarly, Ender et al (2008) used marker-assisted selection for WM-resistance QTL located on chromosomes 2 and 7 in two common bean populations involving ICA Bunsi.…”
Section: Introductionmentioning
confidence: 99%
“…Kolkman and Kelly (23) found that genetic resistance in dry bean is quantitatively inherited and complex because it consists of both disease avoidance and physiological mechanisms. Avoidance is manifested in upright and less dense canopies that create a less conducive microclimate for S. sclerotiorum to colonize blossoms and infect the stems (23,29,33).…”
mentioning
confidence: 99%